Business plan: Step - Márquez, Raúl Ferreira (2022)
This project has the goal of creating a business plan to verify the economic viability of the creation of a blockchain-based social media platform that helps users to combat procrastination on diverse activities. Procrastination has been a part of human existence for centuries and it happens mainly because we want to avoid negative moods. With the emergence of new technologies, a case can be made that this phenomenon has increased as we have millions of contents to choose from, that we can access in a very easy way, as all we have to do is reach in our pockets and unlock our smartphones. Decision paralysis, no social pressure, uncertainty of what to do are just some of the reasons that lead us to procrastinate. Step will be the social media platform that contributes to its user’s awareness of long-term procrastination effects and that helps them tackle it using positive reinforcement methods such as a token economy. In this paper, you will find: A thorough research of the literature on these topics; An explanation of the method used to validate the business idea; A contextual analysis to the companies’ environment and its industry; A brief explanation of how the social media platform will be structured and on its business model; An internal and competitive analysis; An implementation plan on Marketing and Operations. To finalize, a financial analysis will be done to check the viability of the project within its first 5 years of activity.